EFFECTS OF ACTIVE GUMBORO VACCINE OF INTERMEDIATE STRAIN HIGH PATHOGENICITY ON THE MORPHOLOGY OF BURSA FABRICIUS AND THE IMMUNE RESPONSE OF BROILER TO VACCINATION AGAINST NEWCASTLE DISEASE - Charles Rangga Tabbu (Jurnal Sain Veteriner, 1998)
This experiment was designed to study the effects of active Gumboro vaccine of high pathogenicity on the morphology of bursa Fabricius and the immune response of broiler to vaccination against Newcastle disease (ND). This experiment was conducted in 330 broilers, which were vaccinated with aviive Gumboro vaccine of high, intermediate and low pathogenicity (control) at the age of 12 days. Experimental chickens were also vaccinated against ND at the age of 4 and 18 days. Diameter of bursas were measured at day 1st through 7th, 14th, 21th, 28th, 35th post Gumboro vaccination. Evaluation of hemaggutination inhibition (HI) liters against ND virus (NDV) were done only at day 7th, 14th, 2lth, 28th and 35th. Samples of bursa were stained with the method of hematoxylin and eosin (H & E). Pathologic evaluation revealed lesions in the bursa Fabricius of chickens vaccinated with Gumboro vaccine of high pathogenicity as well as changes in the diameter of bursa of lesions in this organ. The HI titers against NDV were lower in the group of chickens vaccinated with Gumboro vaccine of high pathogenicity compared with them of other groups. Results indicated that active Gumboro vaccine of high pathogenicity caused lesions in the bursa,which were similar to lesions caused by exposure to field Gumboro virus.